Bridging the gender equality gap in STEM to transform the pipeline in Africa: the African Research Academies for Women (ARA-W) summer research programme - Yvonne Commodore-Mensah, PhD; Seun Shokunbi; Adaobi Okocha, MPH; Olatide Omojaro; Sope Oguntuyo, MD; Janessa Aneke, MPH; Efe Chantal Ghanney, MD; Melrose Huang; Jessica Asante, BS; Paule Valery Joseph, PhD; Kwadwo Sarpong, BS (Elsevier, 2020)
Background: Although progress has been made in developed countries to increase the representation of women in science, technology, engineering, and mathematics (STEM), women in African countries lag behind. Stark gender disparities exist in STEM in Africa due to economic, environmental, sociocultural, and personal factors. Here, we describe the African Research Academies for Women (ARA-W) summer undergraduate research programme that seeks to reverse the under-representation of women in STEM through fellowship opportunities with mentored training at reputable academic and research institutions. Methods: Applicants are selected through a competitive application process on the basis of academic performance, STEM experience, their personal statement, and career potential. Fellows are paired with established leaders in their fields who provide rigorous mentoring for 8 weeks. Fellows submit weekly progress reports, complete a community service project, and participate in a final presentation. Findings: Since 2014, 65 fellows have completed projects on topics including the transmission dynamics of malaria, in-vitro procedures for evaluating cytotoxicity and use of high-performance liquid chromatography, palliative-care training for caregivers of cancer patients, and converting plastic wastes into biodiesel. Mean age of participants was 20 years and 76%, 11%, and 14% studied science, technology, and engineering, respectively. All fellows attended universities in Ghana at the time of participation. Interpretation: Securing funding to cover the full costs of the programme is a challenge. ARA-W is a volunteer-led organisation, which significantly reduces overhead costs. However, because there is no paid full-time staff, we must be mindful of coordinating responsibilities around teammates' schedules. We plan to increase enrolment by 20 fellows every year, and finalise the development of MentorSpace, an online professional mentorship pairing platform to connect individuals affiliated with ARA-W. Through ARA-W's MentorSpace, fellows can connect with an expanded network both within and outside their fields. New fellows will connect with our alumni network, using their knowledge and experience to open doors for future scholars. We have begun to collaborate with academic institutions in Nigeria to allow our model to be translated across Africa. Funding: Individuals and organisations donate to ARA-W to support our mission.